Perforation of the Nasal Septum in a Colorectal Cancer Patient Treated With Aflibercept: A Case Report - Benitez Fuentes, Javier David; Lopez de Sa Lorenzo, Alfonso; Calvo Elias, Alberto Elpidio; Toledano Rojas, Carmen; Granja Ortega, Monica (Curēus (Palo Alto, CA), 2022)
Aflibercept is an antiangiogenic agent used in patients with metastatic colorectal cancer who have progressed to a first-line oxaliplatin-based regimen. The main adverse effects (AEs) of antiangiogenic agents are fatigue, asthenia, anorexia, hypertension, proteinuria, urinary tract infection, diarrhea, and neutropenia. Other AEs, such as hemorrhage, thromboembolic events, and gastrointestinal perforation, are much less frequent. Nasal septal perforation caused by antiangiogenic agents is even rarer. The published literature on this subject is scarce. Here, we report the case of a 54-year-old male with metastatic colorectal cancer undergoing treatment with leucovorin, fluorouracil (5-FU), irinotecan, and aflibercept who presented with epistaxis and nasal congestion. An otolaryngologist performed a rhinoscopy that revealed a perforation of the nasal septum. Aflibercept was withdrawn first, and local treatment was applied with lubricant and antibacterial lotions. It was considered a non-life-threatening side effect, and given the high risk of not continuing treatment in this patient with a recent recurrence, aflibercept was reintroduced in combination with leucovorin, 5-FU, and irinotecan. The patient continued local treatment and follow-up with medical oncology and otolaryngology with gradual improvement of symptoms. Follow-up was discontinued due to disease progression and death after 16 months of the event.